(3eLehY aj CSeGA HYV GdYdeGA hJCQjN ehGdjOge hhajGJges
(3ChdgG (B:s
(3MSf Hf CHj MSf Hf CHj YHO GdgGOi GdTgjQ HGHf GdeHQO , hgh GHf GdbGVi HOQ GdOjf GdebOSi GdMfHdi , hdO SfI KeGf hKeGfeGFI s
(3BNQgG (B:s
(3eMeO Hf EHQGgje Hf eMeO Ydi GdLhRi eGJ SfI KdGK hKeGfeGFI Yf SJjf SfI s
(3hgj eVWQHI GdJQJjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B366 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(378 (3c(B) s
Keywords: (3GdJGQjNs